2014
DOI: 10.1242/jcs.158204
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide binding by the SNX27 FERM domain regulates localisation at the immune synapse of activated T-cells

Abstract: Sorting nexin 27 (SNX27) controls the endosomal-to-cell-surface recycling of diverse transmembrane protein cargos. Crucial to this function is the recruitment of SNX27 to endosomes which is mediated by the binding of phosphatidylinositol-3-phosphate (PtdIns3P) by its phox homology (PX) domain. In T-cells, SNX27 localizes to the immunological synapse in an activation-dependent manner, but the molecular mechanisms underlying SNX27 translocation remain to be clarified. Here, we examined the phosphoinositide-lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Although initial recruitment of the mutant to the IS was similar compared to that of wild type SNX27, deficiency in lipid binding by the FERM domain impaired the subsequent retrieval of the mutant into endosomal compartments following IS maturation. These results correlate with previous studies showing that PM localization of SNX27 during IS formation is absolutely PDZ domaindependent, 4 and suggest that this additional lipid binding site with a preference for the bi-and triphosphorylated PtdIns derivatives known to be involved in endocytosis, 13 favors SNX27 recycling.…”
Section: Static Dynamic and Polarized Models For Vesicle Traffickingsupporting
confidence: 91%
See 2 more Smart Citations
“…Although initial recruitment of the mutant to the IS was similar compared to that of wild type SNX27, deficiency in lipid binding by the FERM domain impaired the subsequent retrieval of the mutant into endosomal compartments following IS maturation. These results correlate with previous studies showing that PM localization of SNX27 during IS formation is absolutely PDZ domaindependent, 4 and suggest that this additional lipid binding site with a preference for the bi-and triphosphorylated PtdIns derivatives known to be involved in endocytosis, 13 favors SNX27 recycling.…”
Section: Static Dynamic and Polarized Models For Vesicle Traffickingsupporting
confidence: 91%
“…Based on our results in HeLa cells, the FERM-located PtdInsbinding site is not necessary for SNX27 accumulation at the endoplasmic recycling compartment (ERC), a property dependent exclusively on the PX domain. 13 This coincides with results from Tseng et al, who compared SNX27 vesicle-binding abilities to those of other SNX-FERM proteins, and suggested an additional lipid-binding site in SNX27 that was absent in both SNX17 and SNX31. 8 The relevance of this alternative lipid binding site for SNX27 endosomal localization was only apparent in HeLa cells treated with the PI3K inhibitor wortmannin, or when the PX domain was mutated.…”
Section: Static Dynamic and Polarized Models For Vesicle Traffickingsupporting
confidence: 90%
See 1 more Smart Citation
“…This conservation is not so evident in the VPS27 PX domain; yet, the binding sites for the PDZ and PX domains on VPS26 are ~80 Å apart, a distance compatible with the 33-residue linker that connects both domains (Figure 7B). This arrangement would place the FERM domain of VPS27 at the C-terminal end of the PX domain, parallel to the membrane (Ghai et al, 2015), and on the concave side of VPS35. In the case of SNX-BAR proteins, the only PX-BAR tandem structure solved to date corresponds to SNX9 (Pylypenko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SNX27, a member of sorting nexin (SNX) family, is known to regulate the trafficking of endosomal cargo proteins from early endosomes to the cell surface (14-16). SNX27's FERM domain interacts with NPXY motif containing cargoes, whereas its PDZ domain can interact with PDZbinding motifs (PDZbm) at the C-terminus of cargo proteins (15,17). Proteomic studies revealed that the cell surface levels of numerous SLC family proteins including ASCT2 were modulated by SNX27 (15), while structural bioinformatics found that SLC family proteins were one of the most abundant classes of PDZbm-containing SNX27 cargos (18).…”
mentioning
confidence: 99%